6+a/13=23

Simple and best practice solution for 6+a/13=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+a/13=23 equation:



6+a/13=23
We move all terms to the left:
6+a/13-(23)=0
We add all the numbers together, and all the variables
a/13-17=0
We multiply all the terms by the denominator
a-17*13=0
We add all the numbers together, and all the variables
a-221=0
We move all terms containing a to the left, all other terms to the right
a=221

See similar equations:

| (5x+10)+70-360=0 | | (5x+10)+200=360 | | −4x2−3=481 | | *x=208 | | 4x+9=-25 | | |4x|+9=25 | | -30=7(5r+6) | | -4x-16=x-5 | | G(-2)=-3x+1 | | -4x-2x+2=-16 | | 7q+5q-10q=2 | | 9r-7r=14 | | –5b−3=–b−6b+9 | | 6.8x-126=180 | | −6(2a/1)=90 | | 7(-3)-(-2m)=0 | | 13=5+x/2 | | x+111=103 | | x+111+103=180 | | 5=-5/9+w | | 20j-16j=12 | | y=-3(-9)-6 | | 0.1x-13.9=0.04x+10.7 | | 5x²+1=50 | | 25=-21x+32 | | 29.5-5.5x=7,5(3x+3.5x) | | 5(x+3)=4(2x14)-1 | | 4(t−13)−–3=19 | | -2(x+20)=64 | | 22/5m=26 | | 7+28x=35 | | 36/6x=6 |

Equations solver categories